2018
DOI: 10.1038/s41598-018-29104-3
|View full text |Cite
|
Sign up to set email alerts
|

Lethal and sub-lethal effects of the insecticide fipronil on juvenile brown shrimp Farfantepenaeus aztecus

Abstract: Chemical pesticides are widely used around the world, but at the same time, they may cause direct or indirect risks to many non-target organisms. Recent increased use of insecticides in coastal areas, for example to control invasive tawny crazy ants, raises concern that insecticides may affect ecologically and/or commercially important species found in estuaries. Here, we investigated the lethal and sub-lethal effects of fipronil on juvenile brown shrimp Farfantepenaeus aztecus over 29 days at five different n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 63 publications
1
6
0
Order By: Relevance
“…It is possible that blocking the GABA-regulated chloride channels in neurons resulted in overexcitation of neurons innervating daphnid muscles of second antennae responsible for swimming activity which led to spastic paralysis as it was found in insects (Hossie et al 1995 ). Similar results were obtained by Al-Badran et al ( 2018 ) who found reduction of locomotor activity in juvenile brown shrimp Farfantepenaeus aztecus with specific movement disturbances such as swimming in circles. Our results also seem to be in agreement with those obtained by Hussain et al ( 2020 ) who demonstrated depression of Daphnia magna locomotor activity after the exposure to FIP at a concentration of 0.117 μg/L.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It is possible that blocking the GABA-regulated chloride channels in neurons resulted in overexcitation of neurons innervating daphnid muscles of second antennae responsible for swimming activity which led to spastic paralysis as it was found in insects (Hossie et al 1995 ). Similar results were obtained by Al-Badran et al ( 2018 ) who found reduction of locomotor activity in juvenile brown shrimp Farfantepenaeus aztecus with specific movement disturbances such as swimming in circles. Our results also seem to be in agreement with those obtained by Hussain et al ( 2020 ) who demonstrated depression of Daphnia magna locomotor activity after the exposure to FIP at a concentration of 0.117 μg/L.…”
Section: Discussionsupporting
confidence: 90%
“…In zebrafish embryos, larvae and adults adverse changes of behavioral parameters and oxidative stress were also found (Stehr et al 2006 ; Bevilaqua et al 2020 ). FIP also induces toxic effects in marine and freshwater crustaceans such as estuarine copepod Amphiascus tenuiremis (Chandler et al 2004 ), kuruma prawn, sand shrimp, and a surrogate mysid species Americamysis bahia (Hano et al 2019 ), blue crab Callinectes sapidus (Goff et al 2017 ), juvenile brown shrimp Farfantepenaeus aztecus (Al-Badran et al 2018 ), and grass shrimp Palaemonetes pugio (Key et al 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…Around the world, pesticides are widely used to control plant and animal pests but they have direct and/or indirect toxic effects on beneficial organisms 1 . Among pesticides, fipronil (FIP) [5-amino-3-cyano-1-(2,6-dichloro-4-trifluoromethylphenyl) 4-fluoromethylsulfinyl pyrazole] is a second-generation phenylpyrazole insecticide 2 extensively used in the veterinary clinical field against many pests, and ectoparasites 3 , 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Although most studies have concentrated on the impact of fipronil in the phylum Arthropoda (insects, arachnids and crustacea), it is also toxic for other taxa in the phyla mollusks and Cnidaria (Figure 1). Laboratory studies of the coastal brown shrimp, Farfantepenaeus aztecus, estimated a fipronil 96-hr LC50 of 1.3 ppb (Al-badran et al, 2018). However, at concentrations from 0.1 ppb to 10 ppb, survival was progressively reduced to the point that all individuals died after 28 days of exposure.…”
Section: Introductionmentioning
confidence: 99%